Geronimo and the Apache resistance (WGBH Educational Foundation, 2007)
Descendants of legendary Native American leader Geronimo tell the story of a half-century of war, displacement, confinement, and finally resistance that ended with the decimation of the Chiricahua Apaches and the loss of their traditional homeland in the Southwest. Geronimo is revealed as a shrewd leader, formidable fighter, and poetic shaman--dedicated to a crusade to keep his ancestral land, repeatedly defying and eluding federal authorities. When the government finally forced his surrender in 1886, the Apaches were prisoners, moved to reservations in Florida and later Oklahoma. Their homeland was never returned to them. The film tells an unpleasant story of cruelty, prejudice, and betrayal, and of a tragic collision of two civilizations, each with startlingly different views of one another